(untitled) (Research, Society and Development, 2020)
This study aimed to determine the frequency of gastrointestinal parasites and hemoparasites in dogs and cats, seen at the Veterinary Hospital of the Federal University of Pelotas. 114 fecal samples (90 from dogs and 24 from cats) and 101 blood samples (93 from dogs and 8 from cats) were analyzed. The coproparasitological techniques used to analyze the material were: Willis Mollay (1921), Faust (1938) and Hoffmann, Pons and Janer (1934). Of the fecal samples of dogs, 50/90 (55.5%) were positive for gastrointestinal parasites, with Ancylostoma being the prevalent genus. Of the cat samples, 10/24 (41,7%) were positive and Toxocara was the most observed gender. Of the blood samples from dogs, 33/93 were positive for hemoparasites (35.5%), with Babesia being the prevalent gender. Of the cat samples, only 1/8 was positive (12.5%), with Mycoplasma being the observed gender. The results obtained in this study show that there is a high frequency of gastrointestinal parasites and hemoparasites in the animals served, making it necessary to adopt preventive measures, such as endo and ectoparasite control and also to perform coprological exams and to investigate hemoparasites as a routine of the animals that comes to care.